Decentralized lab testing. - Miller CM; Niznik C (Hospital Topics)
What is involved in setting up and managing a decentralized laboratory testing program at a hospital? What elements are involved in making such a program a success? Multidepartmental and multidisciplinary cooperation and communication are the keys to implementing a cost-effective, user-friendly system that assures quality patient care and operator competence.